PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN NILAI PELANGGAN SEBAGAI VARIABEL MEDIASI - Nikko Indra Pradika, Ernawati & Erni Widajanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The purpose of this study was to analyze the effect of service quality and cusotmer value on loyalty and analyze the effect of the service quality on cusomer loyalty mediated by customer value. This study is a survey. Population are customer Popeye Chicken Express Nusukan 1 Surakarta. Sample as many as 100 people with purposive sampling and convenience sampling. The type of data used quantitative and qualitative data. Sources of data used primary data and secondary data. The technique of collecting data used questionnaires, observations and literature. Data were analyzed used path analysis. The survey results revealed that the service quality has a significant effect on customer loyalty. Service quality has not a significant effect on customer value. Customer value has a significant effect on customer loyalty. Customer value mediate the effect of service quality on customer loyaltyKeywords: service quality, customer value, loyalty